Studi Deskriptif: Penatalaksanaan Pembidaian pada Pasien Fraktur di Unit Gawat Darurat Puskesmas Kayangan - Ni Nyoman Santi Tri Ulandari Ni Nyoman Santi Tri Ulandari; Nia Firdiyanti Nia Firdiyant; Wahyu Cahyono Wahyu Cahyono; Ageng Abdi Putra Ageng Abdi Putra; Tina Mustika Tina Mustika (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Fractures are musculoskeletal emergency cases that are often found in health facilities such as the Kayangan Community Health Center where traffic accident cases in 2023 will increase every month, January 27 cases, February 37 cases, March 32 cases, April 25 cases, and the most accident cases are in May 48 cases. Objective: The aim of this study was to find out descriptions of the management of splinting for fracture patients in the ER at the Kayangan Community Health Center, North Lombok Regency. Method: The type of research used is quantitative research with a descriptive analytical research design. The population in the study were all ER nurses at Kayangan Community Health Center with a total of 13 sampling techniques. The research instrument used was an observation sheet, data analysis used univariate. Results: The results of the 13 respondents who were observed obtained the results of splinting management for fracture patients with management according to the SOP for 10 respondents and not according to the SOP for 3 respondents. Conclusion:  It is recommended that healthcare professionals continue to improve patient care regarding self-care management in controlling hypertension.